KAJIAN “GERTAK TUNDUK” SEBAGAI INOVASI ADMINISTRASI KEPENDUDUKAN WARGA NGANJUK (STUDI KASUS PADA KANTOR KECAMATAN NGETOS) - Nurkumala, Dhea Angelia; Eprilianto, Deby Febriyan (Publika, 2024)
Effective and responsive public services are the key to a country's progress, so service providers need to pay attention to several factors in increasing trust, community welfare and sustainable development. The Nganjuk Regency Government created a new breakthrough by holding the Simultaneous Movement to Complete Population Administration (Gertak Tunduk) for Nganjuk Residents which provided population administration services and activated Digital Population Identity (IKD) in all villages, sub-districts and sub-districts. This research uses descriptive research methods with a qualitative approach. The research focus uses the implementation stage theory of the innovation process according to Bland, et al., (2019) with the research focus at the Ngetos District Office. The data collection techniques used were interviews, observation and documentation. Data analysis was carried out by the author using data collection, data reduction, data presentation, and drawing conclusions. The results of this research are that the implementation of the Nganjuk Residents' Submissive Action innovation at the Ngetos District Office has gone well but is not yet optimal. The provision of resources in the form of financial support during the implementation of Gertak Tunduk, the placement of human resources with the existence of a data updating team, monitoring and evaluation that have been carried out helped researchers find out the obstacles in Ngetos District which are still far from the IKD achievement targets. Obstacles that arise include inadequate infrastructure, uneven training provision, unclear structures and mechanisms. The suggestions given by researchers are that infrastructure updates are needed in the form of additional laptop devices and KTP recording devices, socialization is needed for the wider community as a form of attracting public enthusiasm and steps to accelerate IKD achievements, a review is needed regarding the timeline and remaining targets for implementing the Nganjuk Residents' Subordination Action.